Evaluating the association between urban green spaces and subjective well-being in Mexico city during the COVID-19 pandemic. (July 2021) - Mayen Huerta, Carolina; Utomo, Ariane
Abstract: This paper examines the association between the frequency of use of urban green spaces (UGS) and the subjective well-being (SWB) of Mexico City's residents during the COVID-19 pandemic. We conducted an online survey (N = 1954) regarding individuals' perceptions and use of UGS and their SWB, evaluated through the short version of the Warwick–Edinburgh mental well-being scale. Multilevel mixed-effects regression analyses were performed to investigate the association between the frequency of UGS use and SWB, including individual and municipal level characteristics as covariates. Our results suggest that respondents who used UGS once or more per week during the pandemic reported higher SWB scores (8.7%) than those with zero visits. These findings have public policy implications that could enhance the role of UGS in urban environments during times of crisis. Highlights: Frequent use of UGS during the COVID period was positively associated with better SWB. The perceived quality of UGS in the neighborhood also acted as a correlate of SWB. Overall, UGS use was associated with maintaining or increasing SWB during the COVID-19 pandemic. Promoting UGS use may be a path to increasing SWB not only during the pandemic context but also under normal circumstances.